1994
DOI: 10.1002/jca.2920090302
|View full text |Cite
|
Sign up to set email alerts
|

Plasma exchange for preeclampsia: II. Unsuccessful antepartum utilization for severe preeclampsia with or without hellp syndrome

Abstract: The application of plasmapheresis/plasma exchange therapy as described in order to prolong very preterm pregnancies in the undelivered patient with severe preeclampsia/eclampsia with or without HELLP syndrome did not produced encouraging results. Patients in general were exposed to additional medical and surgical risk without a corresponding improvement in perinatal outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1
3

Year Published

1994
1994
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 27 publications
0
23
1
3
Order By: Relevance
“…In 1986 fourteen cases of PE with fresh frozen plasma for maternal indications in selected cases of preeclampsia and eclampsia were reviewed with promising results [114] . In contrast, PE did not prolong pregnancy in preterm preeclampsia in a report by Martin et al [115] . In another report, plasma exchange was commenced at 23, 26 and 29 wk of gestation in preeclamptic women and continued until delivery.…”
Section: Plasmapheresis/ Apheresismentioning
confidence: 78%
“…In 1986 fourteen cases of PE with fresh frozen plasma for maternal indications in selected cases of preeclampsia and eclampsia were reviewed with promising results [114] . In contrast, PE did not prolong pregnancy in preterm preeclampsia in a report by Martin et al [115] . In another report, plasma exchange was commenced at 23, 26 and 29 wk of gestation in preeclamptic women and continued until delivery.…”
Section: Plasmapheresis/ Apheresismentioning
confidence: 78%
“…17 Similarly, plasmapheresis to remove circulating antibodies and immune complexes has not prolonged pregnancy in preterm preeclampsia. 18 Because circulating sFlt-1 represents Ͻ20% of the total body sFlt-1 burden, 19 we hypothesized that a selective adsorption column would create a concentration gradient and augment its removal. Herein we characterize the charge of sFlt-1, perform in vitro experiments to test commercially available devices that could adsorb circulating sFlt-1, and then describe our early experience in treating women with very preterm preeclampsia with the goal of prolonging pregnancy.…”
Section: Clinical Perspective On P 950mentioning
confidence: 99%
“…The antepartum use of plasmapheresis or eculizumab is not a part of the usual management plan, though; both modalities were used by Eckford, yet, with limited benefits [13]. Similarly Martin et al also reported on the poor response of PE/HELLP syndrome to plasmapheresis in the antenatal period [14]. Here, the presence of neurologic or renal dysfunction or extremely abnormal laboratory tests (severe thrombocytopenia, severe anemia, very high LDH and increasing creatinine) are findings that point to TTP as the underlying pathology and plasmapheresis must be started even Ramadan et al J Hematol.…”
Section: Discussionmentioning
confidence: 99%
“…In addition there is a possible added-value of enhancement of platelet count as reported by Eckford et al [13], which might be needed when cesarean delivery is planned. If this trial-plasmapheresis could induce a dramatic improvement in the clinical and laboratory parameters within this short trial, which is unlikely with HELLP syndrome [13,14], then we might consider the working diagnosis as TTP, hence plasmapheresis should be continued as indicated with the possibility of adding steroids and rituximab if AD-AMTS-13 results showed acquired-TTP. On the other hand, if no improvement was elicited, then delivery must be done as scheduled (within 24 -48 h) [15].…”
Section: Discussionmentioning
confidence: 99%